Organizational and legal forms of international cooperation of the Republic of Kazakhstan on National Security - Musilimova, K.S. (KSU publ., 2015)
In this article, based on the an analysis of the Law of the Republic of Kazakhstan «On National Security of the Republic of Kazakhstan», «On Combating Terrorism», «On Countering Extremism», other normative legal acts, current issues of organizational and legal forms of international cooperation of the Republic of Kazakhstan on National Security are considered.
Keywords: the Republic of Kazakhstan; national security; the Interpol; the CIS Anti-Terrorist Center; the Regional Anti-Terrorist Structure of the SCO; national security bodies